2019
DOI: 10.1534/genetics.119.302661
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Long Noncoding RNA Interaction Networks: Control Panels for Cell Fate Specification

Abstract: Lineage specification in early development is the basis for the exquisitely precise body plan of multicellular organisms. It is therefore critical to understand cell fate decisions in early development. Moreover, for regenerative medicine, the accurate specification of cell types to replace damaged/diseased tissue is strongly dependent on identifying determinants of cell identity. Long noncoding RNAs (lncRNAs) have been shown to regulate cellular plasticity, including pluripotency establishment and maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 192 publications
(201 reference statements)
0
26
0
Order By: Relevance
“…15,16 Previous studies have shown that some lncRNAs can affect tumorigenesis and development by regulating proto-oncogenes or tumor suppressor genes, important metabolic enzymes, and even miRNAs, and are considered to be tumor-related lncRNAs. [16][17][18] Here, we revealed that lncRNA PTTG3P was upregulated in CRC cancer tissues by lncRNA databases, and could function as an indicator for the prognosis in CRC. Besides, we demonstrated that PTTG3P interference inhibited cell migration and invasion in vitro.…”
Section: Introductionmentioning
confidence: 85%
“…15,16 Previous studies have shown that some lncRNAs can affect tumorigenesis and development by regulating proto-oncogenes or tumor suppressor genes, important metabolic enzymes, and even miRNAs, and are considered to be tumor-related lncRNAs. [16][17][18] Here, we revealed that lncRNA PTTG3P was upregulated in CRC cancer tissues by lncRNA databases, and could function as an indicator for the prognosis in CRC. Besides, we demonstrated that PTTG3P interference inhibited cell migration and invasion in vitro.…”
Section: Introductionmentioning
confidence: 85%
“…Whether the EGFP-ORF3 fusion protein can still bind to these regions requires further study. lncRNAs are non-coding RNAs with a length of more than 200 nucleotides ( 45 , 46 ). lncRNAs play an important role in many life activities, such as dose compensation effect, epigenetic regulation, cell cycle regulation, and cell differentiation regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the EGFP-ORF3 fusion protein can still bind to these regions requires further study. LncRNAs are noncoding RNAs with a length of more than 200 nucleotides [41,42]. LncRNAs play an important role in many life activities, such as dose compensation effect, epigenetic regulation, cell cycle regulation, and cell differentiation regulation.…”
Section: Discussionmentioning
confidence: 99%